Increased miR‐21‐3p and miR‐487b‐3p serum levels during anaphylactic reaction in food allergic children. Issue 6 (7th May 2021) - Nuñez‐Borque, Emilio; Fernandez‐Bravo, Sergio; Rodriguez Del Rio, Pablo; Alwashali, Ebrahim Mohammed; Lopez‐Dominguez, David; Gutierrez‐Blazquez, Maria Dolores; Laguna, Jose Julio; Tome‐Amat, Jaime; Gallego‐Delgado, Julio; Gomez‐Lopez, Alicia; Betancor, Diana; Cuesta‐Herranz, Javier; et al.
Abstract: Background: Anaphylaxis is the most severe manifestation of allergic disorders. The poor knowledge of its molecular mechanisms often leads to under‐diagnosis. MicroRNAs (miRNA) regulate physiologic and pathologic processes, and they have been postulated as promising diagnostic markers. The main objectives of this study were to characterize the human miRNA profile during anaphylaxis and to assess their capacity as diagnostic markers and determine their participation in the molecular mechanisms of this event. Methods: The miRNA serum profiles from the acute and baseline phase of 5 oral food‐challenged anaphylactic children (<18 years old) were obtained by next‐generation sequencing (NGS). From the panel of statistically significant miRNAs obtained, several candidates were selected and analyzed in 19 anaphylactic children by qPCR. We performed system biology analysis (SBA) on their target genes to identify main functions and canonical pathways. A functional in vitro assay was carried out incubating endothelial cells (ECs) in anaphylactic conditions. Results: The NGS identified 389 miRNAs among which 41 were significantly different between acute and baseline samples. The high levels of miR‐21‐3p (fold change = 2.28, P  = .006) and miR‐487b‐3p (fold change = 1.04, P  = .039) observed by NGS in acute serum samples were confirmed in a larger group of 19 patients. The SBA revealed molecular pathways related to the inflammation and immune system regulation. miR‐21‐3p increased intracellularly and in acute phase serum after EC stimulation. Conclusions: These findings provide, for the first time, some insights into the anaphylactic miRNA serum profile in children and point to miR‐21‐3p and miR‐487b‐3p as candidate biomarkers. Furthermore, the SBA revealed a possible implication of these molecules in the underlying molecular mechanisms. Moreover, ECs increased miR‐21‐3p intracellularly and released it to the environment in response to anaphylaxis.